Biomonitoring of Workers Exposed to Volatile Organic Compounds Associated with Different Occupations by Headspace GC-FID. (8th May 2020) - Yaqub, Ghazala; Hamid, Almas; Khan, Nikhat; Ishfaq, Sunaina; Banzir, Asha; Javed, Tayyaba
Abstract : The present study has been undertaken to analyze the total accumulated burden of volatile organic compounds (VOCs) in blood of occupationally exposed workers. The headspace technique combined with gas chromatography with flame ionization detector was used for the quantitative analysis of the different volatile organic compounds (isopropyl alcohol, phenol, benzene, dichloromethane, ethanol, ethyl acetate, and toluene) in 80 blood samples from the workers belonging to different occupations i.e., shoe polish workers, thinner handlers, paint workers, furniture polish workers, petrol station attendants, textile dyeing workers, printing press workers, and dry port workers as biomonitoring is one of the most promising methods for analyzing the individual burden of VOCs. Another purpose of this study was to investigate the correlation between detected concentrations of VOCs and associated health issues reported by the workers of these professions. Results of the study revealed the presence of different VOCs in blood samples of approximately 70 workers out of 80, and statistical analysis proved a strong relationship between the reported work experience, working hours, and diseases and the detected concentrations of respective volatile organic compounds.